Regulating Cyberspace in Vietnam: Entry, Struggle, and Gain - Nguyen, Ha N. (Columbia Journal of Asian Law, 2022)
This study explores the evolution of cyber regulation in Vietnam since its inception, that is from the events of January 1997, when cyberspace first arrived in Vietnam, to the momentous protests instigated by the Cybersecurity Draft Law in June 2018. A Vietnamese cyber regulatory regime is imagined as an analytically constructed regulatory space where different actors enter, struggle, and gain in their pursuit of regulatory interests. The study argues that cyberspace in contemporary Vietnam has aided non-state actors to participate in the law-making and regulatory processes by inducing state actors to respond with cyber laws, regulatory approaches, and measures. Moving beyond the dichotomy of cyberspace as an inevitable tool for liberation or oppression, Vietnamese cyberspace has been both an instrument for non-state actors to participate in lawmaking, and a regulatory measure for state actors to regain control. A sociological landscape in contemporary Vietnam is depicted through the evolution of a Vietnamese cyber regulatory regime, shaped by dynamic interactions between domestic actors. In sharp contrast to the previous image of an authoritarian Vietnam, cyberspace has aided contemporary Vietnam to metamorphose into a more pluralistic society where organically formed social actors co-regulate cyberspace.